Preference for oviposition of Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) in 30 corn genotypes - CASTRO-ORTEGA, LUIS ARMANDO; ROMERO-ROSALES, FELIPE; MIHM, JOHN A. (Revista Colombiana de Entomología, 1994)
In this work was determined the preference of Sitophilus zeamais for ovipositing in 30  corn genotypes, and it also was studied the relationship between oviposition per seed with the total protein content, tryptophan and lysine. The most preferred genotypes for oviposition were: Ejura (1) 7843Q, P11 Dia 1'90, Cacahuacintle (susceptible control), and the P3 Dia 1'90. Also, they had the highest rate of damaged grains. The less preferred and with a lower rate of oviposited grains were the genotypes B25C22- MHS-1-2-b, Across 8765, P7 Dia 1'90, and the Palomero (resistant control). The protein content, lysine, and tryptophan in the sample and in protein had not influence in the oviposition preference of the insect, the adult attraction, or the oviposition rate per kernel.